Strategic Management of the Leadership of Principals and Islamic Religious Education Teachers in Creating a Religious Culture to Improve Student Learning Achievement in State Senior High Schools - Syafriyadi, Syafriyadi; Suharto, Suharto; Anshori, M. Afif (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to analyze the strategic management of school leadership and Islamic Education (PAI) teachers in fostering a religious culture to enhance students' learning achievement at SMAN 2, SMAN 5, and SMAN 10 Bandar Lampung. It uses a qualitative multisite field study design, with school principals as key informants, supported by vice principals, PAI teachers, subject teachers, and students selected through purposive sampling. Data were gathered through in-depth interviews, observations, and document analysis, then analyzed using data reduction, data display, and conclusion drawing. Validity was ensured through triangulation and member checking. The findings indicate that principals implement strategic management through vision-based planning, integration of religious values ​​into school programs, and ongoing evaluation of both academic learning and character development. Each school applies distinct strategies: SMAN 2 integrates religious values ​​into classroom instruction, SMAN 5 emphasizes consistent religious habituation, and SMAN 10 promotes student engagement through religious extracurricular activities. Collaboration between principals and PAI teachers strengthens character building, improves discipline, and increases student motivation and academic performance. Supporting factors include strong leadership commitment, effective teacher collaboration, and a supportive school environment. However, challenges such as limited facilities and diverse student backgrounds remain. Overall, strategic leadership integrated with religious culture development significantly contributes to improving student achievement in senior high schools.